2011
DOI: 10.1001/archdermatol.2010.433
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Melanoma on Patients' Lives Among 562 Survivors

Abstract: To assess the impact of melanoma on the health-related quality of life of patients from the general population up to 10 years after diagnosis and its determinants.Design: A cross-sectional Dutch population-based postal survey among patients with melanoma for the years 1998 to 2008 using the Eindhoven Cancer Registry. Main Outcome Measures:The 36-Item Short-Form Health Survey (SF-36), Impact of Cancer (IOC) questionnaire and specific melanoma-related questions. The SF-36 scores of the cases were compared with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
56
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 24 publications
10
56
2
1
Order By: Relevance
“…Following the results of two previous studies [23,24], we assumed stage 0eII patients who did not relapse to have an impaired melanoma-associated HRQoL for 2 years only. Despite this, the large proportion of patients with localised melanomas who will never relapse accounted for 34.8% of the YLDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the results of two previous studies [23,24], we assumed stage 0eII patients who did not relapse to have an impaired melanoma-associated HRQoL for 2 years only. Despite this, the large proportion of patients with localised melanomas who will never relapse accounted for 34.8% of the YLDs.…”
Section: Discussionmentioning
confidence: 99%
“…Each DW was applicable for a given period of treatment or remission. According to the previous studies [23,24], stage 0eII patients were assumed to have an HRQoL equal to that of the normal population, from 2 years following diagnosis until recurrence or death. The DWs used are presented in Table 1.…”
Section: Disability Weightsmentioning
confidence: 99%
“…Several studies have focused on health-related quality of life (QoL) and mental distress in these patients. The results of these studies are not congruent: Some studies reported that the QoL is similar in both normal population samples and melanoma patients [3,4]; others reported increased mental distress in melanoma patients. Cornish et al [5], in a review of 13 studies of QoL, as well as Kasparian et al [6] and Trask et al [7] showed that about one third of the patients presented clinically relevant distress.…”
Section: Introductionmentioning
confidence: 97%
“…Yet, due to the morbidity associated with approved interferon-based adjuvant therapy, active surveillance is the recommended standard-of-care for the majority of these patients with active treatments commencing only after metastatic disease is confirmed [2]. Consequently, “fear of recurrence”, a spectrum of symptoms that range from mild depression and irritability to debilitating anxiety manifested during the follow-up period [3], is highly prevalent among melanoma survivors [46]. …”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the study of modifiable lifestyle factors with respect to melanoma prognosis is still sparse and has largely been restricted towards describing patterns of post-diagnosis ultraviolet light (UV) exposure and the associated risk of developing second primary melanomas [6, 1619]. Even fewer published studies describe the association between modifiable lifestyle factors and recurrence of the index melanoma.…”
Section: Introductionmentioning
confidence: 99%